Social and physiological peculiarities and professional orientation of medical students - Toussova, O. V.; Shaporov, A. M.; Pavlova, O. V.; Lebedeva, G. G.; Isaeva, E. R. (Uchenye zapiski (Sankt-Peterburgskiĭ gosudarstvennyĭ medit͡s︡inskiĭ universitet im. akad. I.P. Pavlova), 2015)
The article describes personality features, self-regulation patterns and professional orientation of medical students. It represents the results of the study conducted among the fourth year students. The sample is characterized with high enough behavior regulation, extraversion, high learning potential, flexible thinking, following intuition and personal opinion in profession choice. High anxiety as personality feature and stress vulnerability is typical for female students; independence tendency is typical for male students.